Validation of Phase‐Resolved Functional Lung (PREFUL) Magnetic Resonance Imaging Pulse Wave Transit Time Compared to Echocardiography in Chronic Obstructive Pulmonary Disease. Issue 2 (6th December 2021) - Pöhler, Gesa H.; Löffler, Friederike; Klimeš, Filip; Behrendt, Lea; Voskrebenzev, Andreas; González, Cristian Crisosto; Westhoff‐Bleck, Mechthild; Wacker, Frank; Vogel‐Claussen, Jens
Abstract : Background: Phase‐resolved functional lung (PREFUL) magnetic resonance imaging (MRI) pulmonary pulse wave transit time (pPTT) is a contrast agent free, vascular imaging biomarker, but has not been validated in chronic obstructive pulmonary disease (COPD). Purpose: To validate PREFUL with echocardiographic pPTT as a reference standard and to compare arterial/venous pPTT mapping with spirometry and clinical parameters. Study type: Prospective. Population: Twenty‐one patients (62% female) with COPD and 44 healthy participants (50% female). Field Strength/Sequence: 1.5 T; 2D‐spoiled gradient‐echo sequence. Assessment: Three coronal PREFUL MRI slices, echocardiography, and spirometry including forced expiratory volume in 1 second (FEV1, liter) and predicted defined as FEV1 in% divided by the population average FEV1%, were performed. Pulmonary pulse transit time from the main artery to the microvasculature (PREFUL pPTT), to the right upper lobe vein (PREFUL pPTTav, echo pPTTav ), from microvasculature to right upper lobe vein (PREFULvein ) and the ratio of PREFUL pPTT to PREFUL pPTTvein were calculated. Body mass index (BMI), Global Initiative for COPD (GOLD) stage 1–4, disease duration, and cigarette packs smoked per day multiplied by the smoked years (pack years) were computed. Statistical Tests: Shapiro–Wilk‐test, paired‐two‐sided‐t‐tests, Bland–Altman‐analysis, coefficient of variation, Pearson ρ were applied, pPTT data were compared between 21 subjects from the 44 healthy subjects who were age‐ and sex‐matched to the COPD cohort, P < 0.05 was considered statistically significant. Results: PREFUL pPTTav significantly correlated with echo pPTTav ( ρ = 0.95) with 1.85 msec bias, 95% limits of agreement: 55.94 msec, −52.23 msec in all participants ( P = 0.59). In the healthy participants, PREFUL and echo pPTTav significantly correlated with age ( ρ = 0.81, ρ = 0.78), FEV1 ( ρ = −0.47, ρ = −0.34) and BMI ( ρ = 0.56, ρ = 0.51). In COPD patients, PREFUL pPTT significantly correlated with FEV1 predicted ( ρ = −0.59), GOLD ( ρ = 0.53), disease duration ( ρ = 0.54), and pack years ( ρ = 0.49). Data Conclusion: Arteriovenous PTT measured by PREFUL MRI corresponds precisely to echocardiography and appears to be feasible even in severe COPD. Evidence Level: 1 Technical Efficacy: Stage 2